Cartazes de cinema: da publicidade à coleção - Santos, Laís Galvão dos (2012)
Assuming that every cultural artifact has a life story that is particular to itself and whose biographical narrative is constructed by the active intervention of its users and consumers, this work sought to adress the paths that movie poster trails, from its advertising status until singularization within a private collection. This process lies in the set of meanings that acts in and through the cultural, social, historical, technological and individual spheres, and owes much to the intervention of the activities and thoughts of advertising and design. For the object of the movie poster to be understood in its macro-biography, research was made in the history of the poster, graphic arts and cinema, having in mind studies about collections and material culture. In the end, a collection of selected posters from the 1960s, period of time chosen, was presented.